Ethanolamine utilization in Salmonella typhimurium. - Roof, D M (1988)
Ethanolamine can serve as the sole source of carbon and nitrogen for Salmonella typhimurium if vitamin B12 is present to serve as a cofactor. The pathway for ethanolamine utilization has been investigated in order to understand its regulation and determine whether the pathway is important to the selective forces that have maintained the ability to synthesize B12 in S. typhimurium. We isolated mutants that are defective in ethanolamine utilization (eut mutants). These mutants defined a cluster of genes located between purC and cysA at 50 min on the Salmonella chromosome. A genetic map of the eut region was constructed. Included in the map are mutations which affect ethanolamine ammonia lyase, the first degradative enzyme, and mutations which affect the second enzyme in the pathway, acetaldehyde dehydrogenase. Transcriptional regulation of the eut genes was studied by using eut-lac operon fusions created by insertion of Mu d lac. Transcription is induced by the simultaneous presence of ethanolamine and B12 in the growth medium. The eut genes constitute a single unit of transcription. One class of mutations located at the promoter-distal end of the eut operon prevent induction of transcription.